1993
DOI: 10.3382/ps.0720583
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Muscle Chemical Composition, pH, and Protein Extractability Among Eight Different Broiler Crosses

Abstract: Variations in muscle chemical composition, pH, and protein extractability were studied using male broilers of eight different genetic crosses of commercial strains. Three replicate groups of 24 birds of each cross were grown in floor pens using commercial corn-soybean meal diets. At 8 wk of age, three birds per replicate, weighing within 5% of the pen average, were slaughtered, scalded, defeathered, eviscerated, and chilled in ice slurries overnight. Muscles were excised from breasts and thighs, and trimmed of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 13 publications
3
16
0
Order By: Relevance
“…This result is also consistent with the report of Xiong et al (1993). Therefore, the relatively low fat and high ash content of the KNC thigh meat may be considered a unique compositional characteristic.…”
Section: Proximate Compositionsupporting
confidence: 82%
“…This result is also consistent with the report of Xiong et al (1993). Therefore, the relatively low fat and high ash content of the KNC thigh meat may be considered a unique compositional characteristic.…”
Section: Proximate Compositionsupporting
confidence: 82%
“…Lycopene is a lipophilic compounds and thus accumulates more in leg meat, which is characterized by higher ether extract amount than breast meat (Xiong et al 1993;Quentin et al 2003). Lycopene accumulation was mainly studied in laying hens to produce enriched eggs (Olson et al 2008;Gregosits et al 2009;Rotolo et al 2010), while few studies report data on lycopene accumulation in avian tissues or biological fluids.…”
Section: Discussionmentioning
confidence: 99%
“…Wattanachant et al (2004) and Ševčíková et al (2006) found similar levels of fat in breast muscle (1.03 to 1.10 g.100 g −1 ) of hybrid combinations Ross 308, Cobb 500 and Hubbard JV were in commercial and domestic chickens in comparison of our experiment. Xiong et al (1993) found compared with the results of the experiment higher levels of fat in breast muscle (over 2 g.100 g −1 ) in various genetic crossbreeds of broilers. In the thigh part (Table V) were noted the highest average of fat content, like the breast muscle of Ross 308 cocks (10.58 g), lower in Hubbard JV (10.51 g) and lowest in Cobb 500 (10.29 g).…”
Section: Results and Discusionmentioning
confidence: 73%